2009
DOI: 10.1213/ane.0b013e3181beea9b
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Homer1 Proteins in the Spinal Dorsal Horn Are Associated with Loose Ligation of the Rat Sciatic Nerve

Abstract: Background Plasticity in the spinal dorsal horn is thought to underlie at least in part pain behavior following peripheral nerve injury. Homer1 proteins play an important role in synaptic plasticity through an activity-dependent remodeling of the post-synaptic density (PSD). In this study we examined the early consequences of the loose ligation of the sciatic nerve on the levels of Homer1a and Homer1b/c proteins in the PSD of spinal dorsal horn neurons. Methods Male rats were randomly assigned to control, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…Several studies have investigated the role of Homer in neuropathic and inflammatory pain models in both rats and mice. It has been reported that levels of Homer1b/c in the postsynaptic density fraction show an early reduction and then a prolonged increase in the dorsal horn ipsilateral to a chronic constriction (neuropathic) injury ( Miletic et al, 2005 , Miletic et al, 2009 , Obara et al, 2013 ), and a similar prolonged increase was seen following inflammation induced by an intra-articular injection of complete Freund’s adjuvant ( Yao et al, 2011 ). It has also been shown that disrupting the function of Homer1b/c with intrathecally administered antisense oligonucleotides led to a reduction of pain in an inflammatory model ( Yao et al, 2011 , Yao et al, 2014 ), while over-expression of Homer1c/2b in the dorsal horn exacerbated pain in the chronic constriction injury model ( Obara et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have investigated the role of Homer in neuropathic and inflammatory pain models in both rats and mice. It has been reported that levels of Homer1b/c in the postsynaptic density fraction show an early reduction and then a prolonged increase in the dorsal horn ipsilateral to a chronic constriction (neuropathic) injury ( Miletic et al, 2005 , Miletic et al, 2009 , Obara et al, 2013 ), and a similar prolonged increase was seen following inflammation induced by an intra-articular injection of complete Freund’s adjuvant ( Yao et al, 2011 ). It has also been shown that disrupting the function of Homer1b/c with intrathecally administered antisense oligonucleotides led to a reduction of pain in an inflammatory model ( Yao et al, 2011 , Yao et al, 2014 ), while over-expression of Homer1c/2b in the dorsal horn exacerbated pain in the chronic constriction injury model ( Obara et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…Homer1a is the short form of the scaffolding proteins in the Homer1 family that can disrupt the mGluR signaling complex and negatively regulate nociceptive plasticity through an activity-dependent remodeling of the postsynaptic density in spinal cord sensory neurons (33). Thus, unlike approaches for pain management that aim to increase Homer1a expression in nociceptive relay neurons (33,42), we found that HUP-A reduces the release of primary sensory neurotransmitters and inhibits secondary sensory neurons, preventing up-regulation of Homer1a in the DH (Fig. 6 I and J).…”
Section: Discussionmentioning
confidence: 99%
“…6 G and H). Similarly, Homer1a, an activity-dependent inducible dominant-negative form of the linking protein that can disrupt the mGluR-signaling complex and regulate nociceptive plasticity at spinal synapses (33), was significantly lower in the cervical and lumbar DH of HUP-A-treated rats than in controls (Fig. 6 I and J).…”
Section: Histopathology and Immunocytochemical Analyses Of The Spinalmentioning
confidence: 92%
“…That both Homer1a deletion and the Grm5 R/R transgene exacerbate neuropathic pain symptoms, while neither Homer1 nor Homer2 deletion influence pain hypersensitivity (Obara et al, 2013), argues that the severity of neuropathic pain symptoms is not a determinant of CCI-induced deficits in heroin CPP (Table 2). CCI-induced neuropathy likely involves temporally dynamic changes in inducible vs. constitutive Homer expression, with early post-injury elevations in inducible Homers facilitating synaptic rearrangement that is later maintained by injury-induced increases in CC-Homer expression (e.g., Miletic et al, 2005, 2009; Miyabe et al, 2006; Tappe et al, 2006; Ma et al, 2009; Obara et al, 2013). Thus, the genetic interruption of the temporal dynamics of the interplay between inducible and CC-Homer protein expression at glutamate receptors, and likely other Homer-interacting molecules, while not always sufficient to prevent neuroplasticity within pain pathways, appears to be sufficient to prevent whatever mesocorticolimbic neuroplasticity mediating CCI-induced deficits in heroin-conditioned reward.…”
Section: Discussionmentioning
confidence: 99%